Evaluación de un abono liquido en tres dosificaciones en el comportamiento productivo de Remolacha (Beta Vulgaris l.) en el campus Ceasa-utc 2023. - Toapanta Chisaguano, Lizeth Noemí (2023)
In this research project ‟ Evaluation of a liquid fertilizer in three dosages in the productive behavior of beet (Beta vulgaris l.) at CEASA-UTC 2023 campus. " Was held in Campus Salache, canton Latacunga, Cotopaxi province, the research was based on the application of active liquid fertilizer 100 with three different doses of 1litro, 2 liters and 3 liters in 10 liters of water was counted with a witness that allowed me to compare with the three different doses that were evaluated from frequencies, every 15 days, of application. A completely random block design (DBCA) was applied, with 15 experimental units composed of three treatments and three different doses where five plants were evaluated for each experimental unit. The variables evaluated in the postcosecha were: Firmness, soluble solids, weight, and equatorial diameter. The analysis revealed that the best dose that can be applied in beet cultivation is the dose of 3 liters of active liquid fertilizer 100 in 10 liters of water giving a better result in the variable of firmness with the analysis of means by tukey to 5% in the treatments was evidenced two statistical groups being the greater T3 with an average 4.06 firmness, while the T0 (witness) reached an average of 3.04 in firmness. As well as the soluble solids variable showed that, if there is high statistical significance for treatments, similarly in the weight variable three groups were determined in the first group treatment T3 reaching an average of 286.20g being the best reference to the other treatments, the T2 and T1 reached similar averages and the last group was the T0 (witness) which barely reached an average 83g. And its last variable diameter making known that treatment three is the best dose.